The impact of low education and poor health on unemployment varies by work life stage - van Zon, Sander K. R.; Reijneveld, Sijmen A.; Mendes de Leon, Carlos F.; Bültmann, Ute (International Journal of Public Health, 2017)
The aim of this study is to examine associations and interactions of education, and physical and mental health with unemployment in early, mid, and late work life.